Characteristics Environmental and Anopheles Larva Species In High And Low Clinical Malaria Cases In The Landak District of West Kalimantan Province - Bariyah, Khairul; Utomo, Budi; Subekti, Sri; Sustini, Florentina; Juniastuti, Juniastuti; Fathmawati, Fathmawati; Arwati, Heny (Indonesian Journal of Tropical and Infectious Disease, 2021)
Malaria remains a health problem in Indonesia. West Kalimantan is a malaria endemic area with high and lowincidence. Landak District is one of the malaria endemic area. Malaria cases were found in the areas around illegalgold mining and oil palm plantations. The aims of this study were to describe the characteristics of the breeding sitesand species of Anopheles larvae found in high malaria cases area, namely Amboyo Utara Village and low clinicalmalaria cases, area namely Mandor Village. This research is a descriptive research with cross sectional design. Thesamples were Anopheles larvae collected with Accidental sampling technique in the breeding sites. Environmentalcharacterization of breeding sites were physical characteristic including water temperature and sun exposure,chemical characteristic including water pH and salinity, and biological characteristics including water biota. Theresults of this study ware environmental characteristics that have the potential to breed Anopheles mosquitoes inAmboyo Utara Village, including water temperature 26-30ï‚°C, shandy, water pH 5.0-7.6, salinity 0.2-1.0 ppt, biotaswater hyacinth, grass and tadpole. The Mandor village, water temperature 29-30 ºC, shandy, pH of 6.9-8.0, salinity of0.5 ppt, water biota grass. Anopheles species found in Amboyo Utara village were larvae of An. vagus (94.30%), An.tessellatus (3.42%), An. subpictus (1.62%), An. indefinitus (0.81%) and An. maculatus (0.81%). Characteristics ofbreeding sites in Mandor village were larvae of An. maculatus (11.11%), An. subpictus (3.70%), and An. vagus(85.18%). The conclusion of this study was that di erent species found at breeding sites with di erent environmentalcharacteristics in both high and low malaria areas in Landak District, West Kalimantan Province.